2016
DOI: 10.2196/jmir.5725
|View full text |Cite|
|
Sign up to set email alerts
|

Seeing the “Big” Picture: Big Data Methods for Exploring Relationships Between Usage, Language, and Outcome in Internet Intervention Data

Abstract: BackgroundAssessing the efficacy of Internet interventions that are already in the market introduces both challenges and opportunities. While vast, often unprecedented amounts of data may be available (hundreds of thousands, and sometimes millions of participants with high dimensions of assessed variables), the data are observational in nature, are partly unstructured (eg, free text, images, sensor data), do not include a natural control group to be used for comparison, and typically exhibit high attrition rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 51 publications
8
47
0
Order By: Relevance
“…A cluster analysis of the sample revealed two distinct groups of participants – a nondistressed group with an average depression score below the cut‐off (50.5% of the sample) and a distressed group with a depression score well above the cut‐off (49.5% of the sample). Similar results were reported by both Sergeant and Mongrain () and Carpenter et al (). These findings indicate the high relevance of research on the use of PPIs among persons with mental illness, especially among individuals with depression.…”
Section: Introductionsupporting
confidence: 91%
“…A cluster analysis of the sample revealed two distinct groups of participants – a nondistressed group with an average depression score below the cut‐off (50.5% of the sample) and a distressed group with a depression score well above the cut‐off (49.5% of the sample). Similar results were reported by both Sergeant and Mongrain () and Carpenter et al (). These findings indicate the high relevance of research on the use of PPIs among persons with mental illness, especially among individuals with depression.…”
Section: Introductionsupporting
confidence: 91%
“…To measure the real-world effects of using MHapps outside of clinical trials, some have suggested investigating and quantifying positive relationships between app usage and mental health outcomes (Carpenter et al, 2016;Yeager & Benight, 2018). This can help avoid "digital placebo effects," which occur when merely the installation of a MHapp can bias individuals' responses towards favourable mental health outcomes (Torous & Firth, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To be able to compare email counseling in different interventions and/or different study populations, automatic text coding of such large amounts of text data might be beneficial. Different text processing methods exist, such as the software program Linguistic Inquiry and Word Count (LIWC), the latent Dirichlet allocation technique (LDA) (Carpenter et al 2016) and word clouds analysis (McNaught and Lam 2010). However, these methods or programs only detect single words rather than its context (Tausczik and Pennebaker 2010).…”
Section: Practical Implications and Conclusionmentioning
confidence: 99%